Questioning Equity and Excellence in Ontario and Scotland: Critical Policy Analysis of Parent Inclusion for Reducing Educational Inequality - Antony-Newman, Max (Comparative and International Education / Éducation comparée et internationale, 2023)
Over the last three decades many countries made efforts to improve their education systems by increasing students’ academic achievement. A new appreciation of inequality in education among policymakers provided impetus to focus on equity. Parental involvement and engagement in education are vital for students’ academic achievement. If in the context of educational policy, excellence and equity go together, what is the role assigned to parents? A critical policy analysis of seven policy documents from Ontario and Scotland showed that policies acknowledge the crucial role of parents in achieving educational excellence and mention barriers marginalized parents face in engaging with their children’s education. The role of White middle-class nonimmigrant parents in pursuing excellence for their children at the expense of equity for all is neglected. Marginalized parents are seen through the deficit lens. Implications for policy include making parents from dominant groups visible and adopting an asset-based approach to marginalized parents.